If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(f + -18) = -3 Reorder the terms: 3(-18 + f) = -3 (-18 * 3 + f * 3) = -3 (-54 + 3f) = -3 Solving -54 + 3f = -3 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + 3f = -3 + 54 Combine like terms: -54 + 54 = 0 0 + 3f = -3 + 54 3f = -3 + 54 Combine like terms: -3 + 54 = 51 3f = 51 Divide each side by '3'. f = 17 Simplifying f = 17
| (u^2-u-2)/(2u^2-8) | | -2-2y=3-2y+1 | | 52=-x+7x+10 | | x/42-1/7=28 | | 2y+7y-4y= | | (x+5)-(x+3)(x+5)= | | 9x-5x+7=x-7+14 | | 8(g-3)=12g-24 | | 2=-2(v+5) | | 6-5(5v-8)=171 | | x^3-7x^2-58x+150=0 | | (3y+2)(7y)y=-1 | | -3x-10-2x=-25 | | 18-f=5 | | 3-m/6=8 | | 3-(2-f)+1=2(1-f) | | 4x+10+2x=16 | | a-7=-36 | | -11=6+2x-7 | | 3(3x-7)+5=2(2x+12) | | 5y-6-3y+5=0 | | sin9pie/3 | | 81=9x+9 | | 4x-6x+x-4+5x= | | 2/9-31=16=7/9 | | x^2-15x-52=0 | | 9=a/3-4 | | -3b+10(b-4)=-110 | | 8(x+4)-6x=x-2 | | 1-7x-1=-21 | | 5m+10=5m-10 | | -23=-4x-x-8 |